Automated Core And Cavity Design System For Mould Works Using Generative Method Of Computer Aided Process Planning - Md Yusof, Mursyidah (2017)
In recent years, many efforts have been made for core and cavity design system to be fully automated. Three profound limitations in the previous automated core and cavity design systems are (i) the lack in parting direction flexibility, (ii) inability to detect and generate parting direction for both inner and outer undercuts and (iii) no information transfer from automated core and cavity design system to machining system. To overcome these limitations, automated core and cavity design system (ACCDS) is developed. This system acts as a component in computer aided process planning system where it takes information from any 3D CAD model and provides information to the machining system. Generative method is the basis of this system where core and cavity models are generated from scratch. The outputs from the system are (i) the generated core, cavity and side-cores with parting direction and (ii) the information of zero tool-face collision angle range of core and cavity mould pieces. By comparing ACCDS with a recent system proposed by a researcher, improvements such as better core and cavity design and the reduction of system computational time were observed. This shows that ACCDS were able to contribute in the betterment of the core and cavity design system in automatic manner.